Natural History of Pulmonary Subsolid Nodules: A Prospective Multicenter Study. Issue 7 (July 2016) - Kakinuma, Ryutaro; Noguchi, Masayuki; Ashizawa, Kazuto; Kuriyama, Keiko; Maeshima, Akiko Miyagi; Koizumi, Naoya; Kondo, Tetsuro; Matsuguma, Haruhisa; Nitta, Norihisa; Ohmatsu, Hironobu; Okami, Jiro; Suehisa, Hiroshi; et al.
ABSTRACT : Introduction: : The purpose of this study was to evaluate the natural course of the progression of pulmonary subsolid nodules (SSNs). Materials and Methods: : Eight facilities participated in this study. A total of 795 patients with 1229 SSNs were assessed for the frequency of invasive adenocarcinomas. SSNs were classified into three categories: pure ground‐glass nodules (PGGNs), heterogeneous GGNs (HGGNs) (solid component detected only in lung windows), and part‐solid nodules. Results: : The mean prospective follow‐up period was 4.3 ± 2.5 years. SSNs were classified at baseline as follows: 1046 PGGNs, 81 HGGNs, and 102 part‐solid nodules. Among the 1046 PGGNs, 13 (1.2%) developed into HGGNs and 56 (5.4%) developed into part‐solid nodules. Among the 81 HGGNs, 16 (19.8%) developed into part‐solid nodules. Thus, the SSNs at the final follow‐up were classified as follows: 977 PGGNs, 78 HGGNs, and 174 part‐solid nodules. Of the 977 PGGNs, 35 were resected (nine minimally invasive adenocarcinomas [MIAs], 21 adenocarcinomas in situ [AIS], and five atypical adenomatous hyperplasias). Of the 78 HGGNs, seven were resected (five MIAs and two AIS). Of the 174 part‐solid nodules, 49 were resected (12 invasive adenocarcinomas, 26 MIAs, 10 AIS, and one adenomatous hyperplasia). For the PGGNs, the mean period until their development into part‐solid nodules was 3.8 ± 2.0 years, whereas the mean period for the HGGNs was 2.1 ± 2.3 years ( p = 0.0004). Conclusion: : This study revealed the frequencies and periods of development from PGGNs and HGGNs into part‐solid nodules. Invasive adenocarcinomas were diagnosed only among the part‐solid nodules, corresponding to 1% of all 1229 SSNs.